Digital Maturity of HR in SMEs (European Journal of Marketing and Economics, 2024)
Digitalization and digital transformation processes pose chances and challenges to companies in a variety of different aspects. The present paper focuses on the digitalization of HR management in SMEs. The situation if discussed both in the light of SMEs, who are faced with unique challenges in terms of digitalization and its subsequent management. The role of the entrepreneurs/head of SMEs in driving the digitalization process is discussed. In a similar vein, the role HR departments can take both in their own digitalization and in the one of the company is displayed from various points of view, citing evidence that HR departments – especially of SMEs – often lag behind in terms of digitalization, thus not living up to their full potential as internal service partners of companies. An empirical study based on a quantitative survey explored these challenges further. A total of n = 16 experts from HR departments of German SMEs assessed the digital maturity of their own departments. The results show that – in accordance with the findings derived from the literature – HR departments are still struggling with digitalization, barely making use of their data and not connecting yet to other IT systems within the company. Most experts describe the role of their departments as reactive instead of active. These findings are discussed in the light of studies on digital maturity, showing that the situation in Germany/Central Europe for SMEs and their HR departments is a complex one: On the one hand it seems clear, that digitalization can help the companies and departments on a long-term perspective – which, according to some findings, is also well-known to the executives. At the same time, HR departments typically lack the (financial) resources and the involvement to actively work on their digital strategy.
Keywords: digital transformation; digital HR; HR strategy; digital maturity; SMEs